Induced protein profile changes in arsenate tolerant and sensitive pseudomonas fluorescens strains - Shilev, Stefan; López, Almudena Fernández; Prieto, María Sancho; Puebla, Enrique David Sancho (Journal of Environmental Engineering and Landscape Management, 2007)
Pseudomonas fluorescens are gram‐negative, motile, rod‐shaped bacteria known for their metabolic versatility. Many strains of this species possess excellent capability to colonize plant roots, promoting plant growth in soils contaminated with toxic metals. P. fluorescens biotype F is a strain tolerant to arsenic which had been isolated previously from soil contaminated with arsenic and other toxic metals and characterized as a promoter of plant growth and accumulation of arsenic. In the present work we studied the protein profile of this strain together with the profile of a sensitive P. fluorescens CECT 378 in the presence and absence of sodium arsenate using two‐dimensional polyacrylamide gel electrophoresis (2D‐PAGE). The gels were analyzed by PDQuest, while the statistical significance was proved by ANOVA. We found 9 differentially expressed proteins in the tolerant strain ‐ 4 new proteins, 4 upregulated proteins and 1 downregulated proteins in the presence of 1000 ppm As. In the non‐tolerant strain there were 7 differentially expressed proteins ‐ 1 new protein, 3 upregulated proteins and 3 downregulated proteins. The identification of the proteins with MALDI‐TOF is in progress. Proteino profilio pakeitimai, sukelti arseną toleruojančioje ir jautriose pseudomonas fluorescens atmainose Santrauka. Pseudomonas fluorescens yra gramneigiama, judanti lazdelės formos bakterija, žinomas jos metabolinis universalumas. Daugelis šios rūšies atmainų gerai sugeba kolonizuotis augalų šaknyse ir padeda augti augalams toksiniais metalais užterštame dirvožemyje. P. fluorescens biotipas F yra tolerantiškas arsenui, jis buvo atskirtas nuo dirvožemio, užteršto arsenu ir kitais toksiniais metalais ir charakterizuotas kaip augalų augimo aktyviklis bei arseno akumuliatorius. Tirtas šios atmainos proteino profilis kartu su jautriojo P. fluorescens CECT 378 profiliu, kai natrio arsenatas yra ir kai jo nėra, naudojant dviejų dimensijų poliakrilamido gelių elektroforezę (2D-PAGE). Geliai buvo analizuoti PDQuest, statistinė reikšmė patikrinta su ANOVA. Atrasti 9 skirtingai išreikšti proteinai toleruojančioje atmainoje. Netoleruojančioje atmainoje buvo skirtingai išreikšti 7 baltymai. Daug nuveikta identifikuojant proteinus su MALDI-TOF. Reikšminiai žodžiai: arsenas, Pseudomonus fluorescens, toleravimas, proteinai, 2D-elektroforezė, rizobakterijos. Изменения профиля протеина, вызванные толерантными к мышьяку и чувствительными разновидностями pseudomonas fluorescens Резюме. Pseudomonas fluorescens – это грамм-отрицательная, движущаяся бактерия в виде палочки. Известна ее метаболическая универсальность. Большинство разновидностей этого вида способны создавать колонии в корнях растений, способствуя росту растений в загрязненной тяжелыми металлами почве. Биотип P. fluorescens толерантен к мышьяку, ранее выделенному из почвы, зараженной мышьяком и другими токсичными металлами, и характеризуется как активатор роста растений и аккумуляции мышьяка. Нами исследовался профиль протеина этой разновидности совместно с профилем чувствительного CECT 378 P. fluorescens в случае с мышьяком и с применением для электрофореза (2D-PAGE) двухдименсионного полиакриламидного геля. Гель был проанализирован в PDQuest, статистическое значение было подтверждено с помощью ANOVA. Были обнаружены 9 дифференцированно выраженных протеинов в толерантной разновидности при 1000 ppm As. В нетолерантной разновидности были дифференцированно выделены 7 протеинов. Идентификация протеинов с помощью MALDI-TOF продолжается. Ключевые слова: мышьяк, Pseudomonas fluorescens, толеранция, протеин, 2-дименсионный электрофорез, ризобактерия, обработка протеинов. First Published Online: 14 Oct 2010